Saturation method for reflexive common knowledge logic - Pliuškevičius, Regimantas; Girčys, Aurimas Paulius (Lietuvos matematikos rinkinys, 2012)
This paper discusses the use of saturation procedure in order to check looping sequents in reflexive common knowledge logic. Traditional approach states that common knowledge operator is defined by some induction-like axiom and requires the use of some looping sequents. The loopcheck-free saturation-like procedure lets us obtain special loopfree sequents.
Keywords: saturation method; common knowledge logic; reflexive common knowledge logic